Around the neighborhood : a counting lullaby - Thomson, Sarah L.; Christy, Jana (Las Vegas, NV : Amazon Publishing, 2012)
This adaptation of the old nursery poem "Over in the Meadow" introduces neighborhood animals and their young and the numbers one through ten.
AD 590
Accelerated Reader AR
Maine author.
Keywords: Nursery rhymes; Children's poetry